Structure-controlled graphene-encapsulated nickel nanoparticle with tailored work function to steer chemoselective hydrogenation of nitroarenes. (April 2023) - He, W.; Jiang, M.M.; Yu, J.X.; Yan, W.; Zhang, X.Y.; Jiang, R.; Zhao, H.F.; Liu, Y.; Feng, F.; Zhang, Q.F.; Lu, C.S.; Li, X.N.
Abstract: In recent years, novel carbon-layer encapsulation strategies have been emerging for the construction of heterogeneous catalysts. However, the mechanism action of thermos-catalytic systems is still unclear. The synergistic effect of metal particle size and carbon layer quantity on catalytic performance has not been reported. The strategy to control the carbon layer quantity and metal particle size is still a big challenge. Here, we proposed a novel idea to design catalysts connecting the performance and the structure via work function. The direct pyrolysis of organometallic coordination polymer is induced to control the carbon layer quantity and metal particle size of the carbon-encapsulated catalyst. The results show that the reduction in the nickel nanoparticle size and the carbon layer quantity were favorable for pumping electrons from the nickel core. There was a corresponding relationship between the work function of the catalyst and its selective hydrogenation performance of halogenated aromatic nitro compounds. With low carbon-halogen bond dissociation energy, a high work function decreased catalytic selectivity. Therefore, the work function can be served as a bridge connecting to the configurational relationship of catalysts. Graphical abstract: Image 1 Highlights: The simple organometallic coordination polymer–induced strategy fabricated a carbon encapsulated catalyst. The metal particle size and carbon layer quantity of catalyst were controlled. The catalyst performance was predicted by working function and bonds dissociation energy of substrates. The carbon encapsulated catalyst is high activity, acid resistance, high stability, and sulfur resistance.